PESANTREN DAN UPAYA DERADIKALISASI AGAMA - Mukodi Mukodi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
The de-radicalization of Islam in Tremas Islamic boarding school was found to have its continuing momentums from generation to generation. Through cultural practices as: scientific culture, religious culture, social culture, and political culture the seeds of such de-radicalization were disseminated. However, the dynamic fluctuation of extremism both transnationally and internationally became a specific challenge. Furthermore, the massive development of Information and Communication Technology (ICT) significantly impacted on the mindset of Tremas boarding school community. Applying qualitative approach and phenomenological method, this article revealed how the religious de-radicalization in Tremas boarding school was knitted and framed in the practices of daily culture. Such practices were carried out in order to make Islamic generations may wisely behave and act. Moreover, Islam might ocupy as it should be, namely Islam as raḥmatan li ’l-‘ālamīn, love peace, promoting love and affection, as well as non-violence.